Use of Satellite High Resolution Infrared Imagery to Map Arctic Sea Ice. - Barnes,James C.; Chang,David T.; Willand,James H. (1969)
The report presents an evaluation of High Resolution Infrared (HRIR) imagery from the Nimbus I and II satellites for mapping arctic sea ice. Included are investigations to determine the type of ice feature identifiable in these data, the limiting size of features that can be reliably detected, and the applications of HRIR imagery for sea ice surveillance. The major part of the evaluation is devoted to analysis of nighttime HRIR data in the real-time, film-strip format. To assist in the interpretation of the film strips, full-resolution digitized data are analyzed. A sample of daytime measurements from Nimbus II is also examined. (Author)